Icariin Prevents Extracellular Matrix Accumulation and Ameliorates Experimental Diabetic Kidney Disease by Inhibiting Oxidative Stress via GPER Mediated p62-Dependent Keap1 Degradation and Nrf2 Activation - Wang, Kai; Zheng, Xiulan; Pan, Zhenzhen; Yao, Wenhui; Gao, Xin; Wang, Xiniao; Ding, Xuansheng (Frontiers in Cell and Developmental Biology, 2020)
The present study aimed to determine whether icariin could attenuate type 1 diabetic nephropathy (T1DN) induced by streptozotocin (STZ) after 4 weeks or not. Therefore, its therapeutic effect on diabetic kidney disease was investigated in view of reactive oxygen (ROS) and extracellular matrix (ECM) generation in human glomerular mesangial cells under high glucose. To establish the participation and the key role of GPER and Nrf2 in ECM deposition, a combination of G15 (antagonist of GPER) or siGPER and siNrf2 were performed, respectively. The results showed that T1DN can be significantly inhibited by oral icariin, evidenced by improvement of 24 h urinary volume, 24 h proteinuria, microalbuminuria and histopathological changes of kidney. Icariin decreased the levels of intracellular superoxide anion, impeded the generation of fibronectin and increased the expression and activity of antioxidant enzymes in the human glomerular mesangial cells treated with high glucose. It acted as a GPER activator, increased dissociation of Nrf2/Keap1 complexes, combination of Keap1/p62 complexes, Nrf2 translocation to nuclear, Nrf2/ARE DNA binding activity, and ARE luciferase reporter gene activity in glomerular mesangial cells. The Nrf2 inhibitor ML385 or siNrf2 obviously abolished extracellular matrix (ECM) generation inhibited by icariin. Furthermore, icariin-induced Nrf2 activation was mainly dependent on p62-mediated Keap1 degradation, which functions as an adaptor protein during autophagy. The GPER antagonist G15 and siGPER obviously abolished the above effects by icariin. Taken together, the present study demonstrated that the therapeutic effects of icariin on type 1 diabetic nephropathy in rats via GPER mediated p62-dependent Keap1 degradation and Nrf2 activation.